2023
DOI: 10.14336/ad.2022.0912
|View full text |Cite
|
Sign up to set email alerts
|

δ-opioid Receptor, Microglia and Neuroinflammation

Abstract: Neuroinflammation underlies the pathophysiology of multiple age-related neurological disorders. Microglia, the resident immune cells of the central nervous system, are critically involved in neuroinflammatory regulation and neural survival. Modulating microglial activation is thus a promising approach to alleviate neuronal injury. Our serial studies have revealed a neuroprotective role of the δ-opioid receptor (DOR) in several acute and chronic cerebral injuries by regulating neuroinflammation and cellular oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 135 publications
(246 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies had provided evidence that an elevation in M2 phenotype microglia following SAH was linked to a more favorable neurological outcome, which indicated that a promising approach for microglia-mediated neuroinflammation in SAH was regulating microglial phenotype from M1 to M2 [ 18 , 50 , 51 ]. However, the specific mechanisms and modulators were not completely understood [ 52 ]. To further evaluate the microglial response status following SAH, we utilized skeleton analysis and fractal analysis with immunofluorescence for Iba1 to assess microglial morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies had provided evidence that an elevation in M2 phenotype microglia following SAH was linked to a more favorable neurological outcome, which indicated that a promising approach for microglia-mediated neuroinflammation in SAH was regulating microglial phenotype from M1 to M2 [ 18 , 50 , 51 ]. However, the specific mechanisms and modulators were not completely understood [ 52 ]. To further evaluate the microglial response status following SAH, we utilized skeleton analysis and fractal analysis with immunofluorescence for Iba1 to assess microglial morphology.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling pathway also mediated the neuroprotective effects of SNC-121 and biphalin in the retinal ganglion of glaucoma models and in the brain of a neonatal cerebral ischemia model, respectively [66,72]. Although the mechanism of signal activation by DOR has not been clearly identified [73], it is possible that DOR agonists exert their effects via a signal distinct from that of the cAMP pathway. The second hypothesis is that SYK-623 potentiates the action of endogenous agonists through its receptor-upregulating effects, a commonly observed property of inverse agonists [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have summarized advances in the dynamics of the extracellular matrix and the regulation of intracellular transcription factors [ 129 , 130 ]. A growing body of research has shifted focus toward the role of neuroinflammation, providing novel insights that could potentially impede or inhibit the progression of such age-related brain disorders [ 131 , 132 ]. MSCs, particularly the MSCs-based cell-free therapy, have emerged as a potent therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%